Híbridas y Quimeras: noise and collective sorority in Mexico City - Mora Flores, Ana Alfonsina (2021)
The soundscape of Mexico City is so rich and eclectic that produces a cacophony perceived as noise by those who inhabit and transit it. Over the last decades, noise has been associated subversive artivist, counter-hegemonic and free expression practices. This work aims to share the progress, observations and reflections of the current research from an interdisciplinary, and gender perspective approach thorugh the case of study of the creation, production and release practices of the feminist collective Híbridas y Quimeras. Noise drives this collective made up of women and dissents, which creates spaces not only by the sound to create, but also by the sorority as a way to raise their voices against patriarchial dynamics still present in the Mexican experimental music scene. In this way, noise is not only the medium, but the message to be heard.